ANALISIS IMPLIKATUR PERCAKAPAN DALAM PROSES PEMBELAJARAN BAHASA INDONESIA KELAS VII - 1 SMP TAWAKKAL DENPASAR (SEBUAH KAJIAN PRAGMATIK) - Fitri Ayu Ambarawati; I Nyoman Adi Susrawan; Dewa Gede Bambang Erawan (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2021)
This study aims to describe and explain about (1) The form of conversational implicature that appears in the process of learning Indonesian in class VII - 1 of Tawakkal Depasar Junior High School, (2) Implications of conversational implicature on the process of learning Indonesian in class VII - 1 of Tawakkal Depasar Middle School are theoretical implications, pedagogical implications, practical implications, (3) Factors that lead to the emergence of conversational implications in the process of learning Indonesian in class VII - 1 of Tawakkal Depasar Junior High School. The research approach used is a descriptive qualitative research method. The subjects of this study were students and Indonesian Language Teachers who were teaching grades VII - 1 of Tawakkal Middle School, Denpasar. The results of this study found the forms and factors as well as the implications of conversational implicatures, namely: conventional implied form, special implied form, general implied form, scale implied form. The underlying factors are language, intimacy, sensitivity, culture, caring and compassion. The implications include the theoretical implications, pedagogical implications, practical implications.